The Walters songwriter's emotions and feelings of "I love you so" - Puspitasari, Monica Indriyani; Baity, Aprilia Nurul; Jupply, Donald (Diksi, 2022)
This study is aimed to analyze the Systemic Functional Language represented in "I Love You So" by The Walters through a transitivity system. The object of the study is taken from the lyric of the song "I Love You So". This study uses a descriptive qualitative research method and note-taking technique by paying attention to the process used in the lyrics. The researchers of this study use triangulation to detect the validity of the data. The result of this study shows that the songwriter desires to convey his emotion and feeling to the woman depicted in the lyrics of the song "I Love You So".Keywords: SFL, transitivity, The Walters